KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMBINAAN PROFESIONALISME GURU DI TAMAN KANAK-KANAK ABA BAYEN PURWOMARTANI KALASAN SLEMAN (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
School principal leadership is an important thing to improve the professionalism of teacher. This study aims: (a) to know the leadership style of school principal; (b) to know the role of school principal’s leadership improve the teacher’s professionalism; (c) to know the teacher’s professionalism in ABA Kindergarten Bayen Kalasan. This study is descriptive qualitative approach. It was held in ABA Kindergarten Bayen Purwomartani Kalasan Sleman Yogyakarta. The respondents in this study are school principal, vice school principal, teachers and school committee of ABA Kindergarten Bayen Kalasan. The methods used to collect the data are observation, interview and documentation. The method used to analyze the data is descriptive qualitative with interactive model from Miles and Huberman who divided the analysis activities through: data collection, data reduction, data display and data verification/conclusion. The study shows that the style of school principal leadership at ABA Kindergarten Bayen Kalasan has had a democratic style, although in certain condition, school principal has an authoritarian and libertarian style. The school principal has been being democratic in the discussion in making decision, always listen to the teacher’s opinion, giving solution for any problem and supporting the teacher. The school principal can be authoritarian toward regulations and in increasing discipline for school administration and also in the school’s rules. Interestingly, the school principal has been using three principals of Ki Hajar Dewantara in applying her leadership styles, those principals are give a good example in the front, support in the middle and give freedom in the back (ing ngarso sung tuladha, ing madya mangun karsa, tut wuri handayani). With those leadership styles, the school principal has been doing her roles to build teacher’s professionalism as an educator, manager, motivator, innovator, leader and supervisor. With those roles, theschool principal had increased the professional competencies in process, pedagogic, personal and social.